Effect of estrogen estrone on uterine and adipose tissue under obesity - Valle, María Ivone (2023)
Previously we reported that, estrone (E1) counteracts uterine oxidative stress induced by an inflammatory environment. In this work, using an experimental model of obesity, the direct action of E1 on uterus (Ut) and adipose tissue (AT) was evaluated. In order to rule out the influence of the hormonal impact during estrous cycle, animals were bilaterally ovariectomized (OVX). Rats were fed with high-fat diet (OVX-Ob) for 10 weeks. After isolation, Ut and retroperitoneal AT explants were in vitro expose to 10 nM E1. Histological analysis of Ut explants (H&E staining) showed that in non-OVX rats exhibited a thicker endometrial layer with great amount of uterine glands compared to uterus sections from OVX rats, verifying the absence of estrous cycles in OVX group. The serum biochemical evaluation showed that, Ob rats exhibited higher levels of serum H2O2; TBARS, and leptin than non-obese (8; 65; 122% above non-Ob, respectively, p< 0.05), profile compatible with obesity. After E1 treatment (4h), Ut slices exhibited an enhancement in nitric oxide synthesis (33% above control P<0.001) and reduction in ROS production (30% below control, P<0.01). To assess whether the effect of E1 on H2O2 generation depends on its ability to enhance NO synthesis, an irreversible NOS inhibitor (L-NAME) was employed. In the presence of L-NAME, the reduction on ROS production elicited by E1 was blocked, suggesting NO dependence. Indeed, in OVX-Ob rats the steroid treatment stimulates uterus angiogenesis. Concomitantly, on AT explants isolated from OVX-Ob rats, E1 prompted an antioxidant action. E1 reduced H202 secretion (2375±263 vs 1978±241 nmol/g AT, C vs E1 p<0.05), and TBARS released (502±195 vs 353±30 nmol/g AT, C vs E1 p<0.05). Indeed, a 14% reduction on leptin secretion was also detected (p<0.05). The results presented evidenced that adipose tissue is targeted of E1 action, and that under obesity the hormone exerts a protective action on Ut and AT reducing oxidative stress.